Potential of advanced microporous zeolites and mesoporous materials derived from natural precursors as supports for iron phosphide catalysts in bio-jet fuel production from palm oil ( Elaeis guineensis ) - Worapak Tanwongwan; Ruttasart Sartsamai; Rungnapa Kaewmeesri; Kajornsak Faungnawakij; Nuwong Chollacoop; Suttichai Assabumrungrat; Masayoshi Fuji; Apiluck Eiad‐ua (RSC Advances, 2025)
) and the excellent acidity of this zeolite, which helped prevent FeP overloading and promote uniform metal distribution. Furthermore, it exhibited remarkable stability and reusability, with performance improving over three consecutive reaction cycles, LHCs yield increasing to 50% and bio-jet selectivity stabilizing at about 83%, attributed to enhanced acidity accessibility and progressive formation of the FeP active phase.
Keywords: Catalysis and Hydrodesulfurization Studies; Zeolite Catalysis and Synthesis; Catalysis for Biomass Conversion